2004
DOI: 10.1159/000080213
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid in the Treatment and Prevention of Skin Diseases: Molecular Biological, Pharmaceutical and Clinical Aspects

Abstract: The glycosaminoglycan hyaluronic acid (HA), or hyaluronan, is a major component of the extracellular matrix of skin, joints, eye and many other tissues and organs. In spite of its simple structure, HA demonstrates remarkable rheological, viscoelastic and hygroscopic properties which are relevant for dermal tissue function. Biological activities in skin, however, are also due to its interaction with various binding proteins (hyaladherins). Due to an influence on signaling pathways, HA is involved in the wound-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 111 publications
2
131
0
10
Order By: Relevance
“…Therefore, in healing of chronic wounds elimination of ROS could be an important strategy and estimation of antioxidants like superoxide dismutase (SOD), catalase (CAT) etc., in granulation tissue becomes relevant as they help destroy free radicals and hasten the process of wound healing. 65,66 In our study ELEHR treated groups showed potent in-vivo antioxidant activity by reducing free radicals stress and thus ELEHR could help to prevent oxidative damage and promote the healing process. In burn wounds, the repair process is more complicated as there is an extensive loss of cells and tissues compared to an incision wound.…”
mentioning
confidence: 54%
“…Therefore, in healing of chronic wounds elimination of ROS could be an important strategy and estimation of antioxidants like superoxide dismutase (SOD), catalase (CAT) etc., in granulation tissue becomes relevant as they help destroy free radicals and hasten the process of wound healing. 65,66 In our study ELEHR treated groups showed potent in-vivo antioxidant activity by reducing free radicals stress and thus ELEHR could help to prevent oxidative damage and promote the healing process. In burn wounds, the repair process is more complicated as there is an extensive loss of cells and tissues compared to an incision wound.…”
mentioning
confidence: 54%
“…HA is involved in the process of wound healing, keratinocyte proliferation (31,32), and angiogenesis (33). In a recently performed study, elevated RHAMM expression correlated with inflammation after bleomycin injury (33).…”
Section: Discussionmentioning
confidence: 99%
“…Its osmotic capability restores tissue hydration during the inflammatory process, and its viscosity helps to prevent the passage of bacteria and viruses into the pericellular area (around the cell). It is a known stimulator of the inflammatory process because it acts as a barrier to tissue degradation and has antioxidant properties, including the ability to eliminate free radicals [32][33][34], which are tissue-damaging byproducts derived from the metabolism of oxygen that can cause inflammation and cancer [35].…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%